Diffuse Panbronchiolitis in a Caucasian Man in Canada. Issue 8 (3rd December 2003) - Sandrini, Alessandra; Balter, MS; Chapman, Kenneth R
Abstract : Diffuse panbronchiolitis (DPB) is a rare, chronic bronchiolar disease in non-Asian populations and is therefore commonly overlooked in Western countries. It usually affects nonsmokers and manifests as persistent air flow obstruction, chronic cough and interstitial nodular opacities. Untreated, the prognosis is poor. In this report the authors describe a Caucasian man of Canadian descent who presented with progressive clinical and lung function impairment despite three years of bronchodilator and corticosteroid treatment with presumed asthma. His chest computed tomography scan showed diffuse centrilobular opacities. Lung biopsy revealed chronic bronchiolitis characterized by infiltration of lymphocytes, plasma cells and foam cells in respiratory and terminal bronchioles, compatible with a diagnosis of DPB. After two months of therapy with clarithromycin, the patient had already shown improvement. Physicians should be aware that DPB may occur in Western countries, and that DPB should be considered in the differential diagnosis of patients with persistent air flow obstruction and nodular shadows on chest radiograms.